Nanogenerators: Transparent Flexible Graphene Triboelectric Nanogenerators (Adv. Mater. 23/2014). (June 2014) - Kim, Seongsu; Gupta, Manoj Kumar; Lee, Keun Young; Sohn, Ahrum; Kim, Tae Yun; Shin, Kyung‐Sik; Kim, Dohwan; Kim, Sung Kyun; Lee, Kang Hyuck; Shin, Hyeon‐Jin; Kim, Dong‐Wook; Kim, Sang‐Woo
<x xml:space="preserve">Abstract</x> Transparent, flexible graphene triboelectric nanogenerators, as a new energy‐harvesting application of graphene, are successfully demonstrated by S.‐W. Kim and co‐workers on page 3918. The work function and friction are decisive factors in understanding the difference in output performance, and depend on the number of layers of graphene. A liquid‐crystal display (LCD), lightemitting diodes (LEDs), and an electroluminescent (EL) display can be powered using the electrical power output of the graphene triboelectric nanogenerator without any external energy source. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>